Xiong Style Taiji in Taiwan: Historical Development & A Photographic Exposé Featuring Master Lin Jianhong - DeMarco, Michael A. (Revista de Artes Marciales Asiáticas, 2012)
This article presents a branch of Yang Family Taijiquan that is little-known outside of Taiwan. It is called Xiong Style after Xiong Yanghe (1888 ~1981). However, what little that has been published in English about Master Xiong is confusing and sometimes contradictory. By utilizing Chinese published sources (including Xiong’s own published writings), unpublished documents by his leading disciples, related websites in Taiwan, personal observations, and photographic documentation, information assembled here should provide a comprehensive overview of Xiong Style Taiji. English language sources are utilized to provide the socio-political setting that had a profound impact on the early Yang Family Taiji development. The main conclusions concern Xiong’s lineage, his preservation of the art, and its significance for the understanding of all taijiquan branches as a martial art and exercise for health.